2020
DOI: 10.3390/ijms21010319
|View full text |Cite
|
Sign up to set email alerts
|

Extended Cleavage Specificities of Two Mast Cell Chymase-Related Proteases and One Granzyme B-Like Protease from the Platypus, a Monotreme

Abstract: Mast cells (MCs) are inflammatory cells primarily found in tissues in close contact with the external environment, such as the skin and the intestinal mucosa. They store large amounts of active components in cytoplasmic granules, ready for rapid release. The major protein content of these granules is proteases, which can account for up to 35 % of the total cellular protein. Depending on their primary cleavage specificity, they can generally be subdivided into chymases and tryptases. Here we present the extende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The proteins before and after cleavage were separated on a 4–12% SDS-PAGE gel. The recombinant enzymes the human chymase, the dog chymase, rMCP-1, the opossum chymase and platypus granzyme B used in this analysis have been described previously [ 10 , 22 , 23 , 34 , 35 ].…”
Section: Figurementioning
confidence: 99%
“…The proteins before and after cleavage were separated on a 4–12% SDS-PAGE gel. The recombinant enzymes the human chymase, the dog chymase, rMCP-1, the opossum chymase and platypus granzyme B used in this analysis have been described previously [ 10 , 22 , 23 , 34 , 35 ].…”
Section: Figurementioning
confidence: 99%
“…The third platypus enzyme, granzyme BGH-like, is located on another contig (Figure 1). This enzyme was found to be a classical Asp-ase with a preference for negatively charged residues in the P1 position, similarly to human, rat and opossum granzyme B [52][53][54].…”
Section: Extended Cleavage Specificities Of Chymase-locus-expressed Serine Proteasesmentioning
confidence: 82%
“…We found that two of the platypus enzymes are chymases, named granzyme B and DDN-1-like, and exhibit very similar specificity to that of the human chymase. They both show preferences for Phe and Tyr over Trp and Leu in the P1 position and also show preferences for aliphatic amino acids both N-and C-terminally of the cleavage site [53]. The third platypus enzyme, granzyme BGH-like, is located on another contig (Figure 1).…”
Section: Extended Cleavage Specificities Of Chymase-locus-expressed Serine Proteasesmentioning
confidence: 99%
“…We, therefore, wanted to look deeper into its specificity. We started with phage display as this technique can give a detailed picture of the extended specificity of a protease [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. We tried more than 10 times with the phage display technique and also with a large panel of both chromogenic and recombinant substrates to identify the cleavage specificity of mMCP-8, however, without success why we doubted if our protease was active.…”
Section: Resultsmentioning
confidence: 99%
“…Cleavage of the anticoagulant proteins, hirudin and anophelin, by a panel of mammalian hematopoietic serine proteases.The efficiency in cleavage of three anticoagulant proteins were assayed in a 15 µL sample volume with approximately 1 µg of the anticoagulant protein and varying amount of protease depending on the activity as determined previously. All proteases except mMCP-8 have been described in previous publications (Human chymase[30], Dog chymase[31], rMCP-1[32], Rat vascular chymase (RVC)[33], rMCP-2[34], Hamster chymase[35], Rabbit and Guinea pig Leu-ases[29], Opossum chymase[36], Platypus chymases[37], Human cathepsin G[38], Human proteinase 3 and N-elastase[39], Human mast cell tryptase and mMCP-6[40]. Panel (A) shows the amino acid sequence of hirudin where the cysteines have been marked in red and all negatively charged residues in green.…”
mentioning
confidence: 99%